Plastid phylogenomics and morphological character evolution of Chloridoideae (Poaceae) - Wang, Rong; Zhang, Xue-Jie; Guo, Xiu-Xiu; Xing, Yan; Qu, Xiao-Jian; Fan, Shou-Jin (Frontiers in Plant Science, 2022)
Chloridoideae is one of the largest subfamilies of Poaceae, containing many species of great economic and ecological value; however, phylogenetic relationships among the subtribes and genera of Cynodonteae are controversial. In the present study, we combined 111 plastomes representing all five tribes, including 25 newly sequenced plastomes that are mostly from Cynodonteae. Phylogenetic analyses supported the five monophyletic tribes of Chloridoideae, including Centropodieae, Triraphideae, Eragrostideae, Zoysieae and Cynodonteae. Simultaneously, nine monophyletic lineages were revealed in Cynodonteae: supersubtribe Boutelouodinae, subtribes Tripogoninae, Aeluropodinae, Eleusininae, Dactylocteniinae, supersubtribe Gouiniodinae, Cleistogenes and Orinus, and subtribe Triodiinae. Within the tribe of Cynodonteae, the basal lineage is supersubtribe Boutelouodinae and Tripogoninae is sister to the remaining lineages. The clade formed of Aeluropodinae and Eleusininae is sister to the clade composed of Dactylocteniinae, supersubtribe Gouiniodinae, Cleistogenes and Orinus, and subtribe Triodiinae. The clade comprising Dactylocteniinae and supersubtribe Gouiniodinae is sister to the clade comprising Cleistogenes, Orinus, and Triodiinae. Acrachne is a genus within Eleusininae but not within Dactylocteniinae. Molecular evidence determined that Diplachne is not clustered with Leptochloa, which indicated that Diplachne should not be combined into Leptochloa. Cleistogenes is sister to a clade composed of Orinus and Triodia, whereas the recently proposed subtribe Orininae was not supported. Cynodonteae was estimated to have experienced rapid divergence within a short period, which could be a major obstacle in resolving its phylogenetic relationships. Ancestral state reconstructions of morphological characters showed that the most recent common ancestor (MRCA) of Chloridoideae has a panicle, multiple florets in each spikelet, the peaked type of stomatal subsidiary cells, and a saddle-shaped phytoliths, while the ancestral morphological characters of Cynodonteae are the panicle, peaked type of stomatal subsidiary cells, sharp-cap cell typed and equal-base-cell microhair, and square-shaped phytoliths. Overall, plastome phylogenomics provides new insights into the phylogenetic relationships and morphological character evolution of Chloridoideae.